2022
DOI: 10.1155/2022/1713657
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of FFBP-LM-ANN Based Hourly GHI Prediction Using Environmental Variables: A Case Study in Chennai

Abstract: Sun is the sustainable and abundantly available alternative resource on the planet Earth. The uncertain nature of the source caused due to various environmental factors increases the need to quantify the irradiation potential at the targeted location, especially for power smoothing processes, solar-fed electrical applications, and the utility grid. The irradiation measuring devices lead to appropriate maintenance and more expenses and are ineffective under dynamically varying irradiation conditions. Hence, a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…The best ANNs model formed by the best combination of inputs was indicated by the higher R 2 value and the lower RMSE values (Supriyanto et al 2019, Zhang et al 2020b, indicated by the coefficient of determination and Root Mean Square Error as in equations 1 and 2. (Sushmi and Subbulekshmi 2022).…”
Section: Anns Development Model With Inputs Variation Scenariosmentioning
confidence: 99%
“…The best ANNs model formed by the best combination of inputs was indicated by the higher R 2 value and the lower RMSE values (Supriyanto et al 2019, Zhang et al 2020b, indicated by the coefficient of determination and Root Mean Square Error as in equations 1 and 2. (Sushmi and Subbulekshmi 2022).…”
Section: Anns Development Model With Inputs Variation Scenariosmentioning
confidence: 99%
“…Considering the Hessian and the Jacobian matrix, the LM algorithm is based on the following relation [44,45]:…”
mentioning
confidence: 99%